Automation of Connector Mating to Improve Wire Harness Assembly on Instrument Panel of Trucks - Rahmani, Amir; Praveen Singh, Harshit (My University, 2024)
The assembly of wire harnesses in the automotive industry is predominantly a manual process that presents numerous ergonomic challenges, often resulting in musculoskeletal disorders among operators. One of the significant challenges in this assembly process is the mating of connectors. This thesis aims to automate the mating process to alleviate operator strain and enhance working conditions. This work is part of the Empowering Human Workers in Wire Harness Assembly (EWASS) project, in collaboration with Scania Group, Volvo Group, Volvo Cars, and academic partners including Chalmers University of Technology, University of Skövde, and Fraunhofer Chalmers for Industrial Mathematics (FCC). The research was conducted at the Smart Factory Lab at Scania Group. The focus of the experimentation was the instrument panel of the Scania truck, being manufactured at the Oskarshamn factory, due to identified ergonomic issues at the pre-assembly stations of the instrument panel. A comprehensive study was conducted on current assembly procedures and automation technologies for wire harness assembly. The product development methodology was utilized, following the concept development funnel. Tools such as the function mean tree and morphological matrix were employed to generate concepts, which were then screened using elimination and Pugh matrices. The optimal concepts were further evaluated using the Kesselring matrix. The thesis culminates in the development of a functional setup capable of performing the connector mating process on the instrument panel, providing insights and learnings that can be applied to develop improved products for the automation of wire harness assembly.